Effect of warm mix additives on the interfacial bonding characteristics of asphalt binders. Issue Volume 19:Issued 12(2018) (2nd December 2018) - Kassem, Emad; Garcia Cucalon, Lorena; Masad, Eyad; Little, Dallas
Abstract: The quality of the interfacial bonding between asphalt binder and aggregates plays a significant role in determining the durability of asphalt mixtures. Warm mix asphalt (WMA) modifiers have been used extensively in the last decade primarily to reduce production and compaction temperatures as well as to improve workability of asphalt mixtures. This study aimed to provide better understanding of the effects of these WMA modifiers on the interfacial bonding between asphalt binders and aggregates. The evaluation focused on measuring surface energy of binders in unaged and aged states and aggregates and then calculating energy parameters that describe the potential of a given asphalt-aggregate combination to resist fatigue cracking and moisture damage. Results show that the combination of asphalt-WMA additive, as well as the content applied of WMA additive has a significant impact on the fatigue cracking and moisture damage resistance. The results suggest that it is poor practice to use a given type and percentage of WMA modifier without regard for binder type. Instead, test methods are recommended to evaluate the compatibility of asphalt binder, WMA additive type/content, and aggregates for improved performance at different conditions.